Effect of Heat Sterilization on the Load/Deflection of Heat-activated Orthodontic Wires - Alavi, Shiva; Mousavi, Seyyed Mohammad; Shirban, Farinaz (Orthodontic Journal of Nepal, 2014)
Introduction: Some of the orthodontic wires are heat-activated (H-A) wires; sometimes delivered in non-sterile packages and some of whose properties can be influenced by heat treatment. Objective: To assess the heat sterilization effects on the load/deflection (L/D) properties of H-A orthodontic wires before application. Materials & method: Three groups of H-A wires (3 cm length and 0.016 inches diameter) were selected; Group A: Nitinol H-A, Group B: H-A memory wire, Group C: Sentalloy H-A. Forty five samples of each type were prepared and randomly divided into three equal groups of 15 wires. Group 1 was selected as control, Group 2 was sterilized by dry heat (2 hours, 160°c) and Group 3 was sterilized using steam heat (15 PSI, 24 min, 121°c). A universal testing machine was used to determine the load/deflection curve of the samples while immersed in 37°c water bath using 3-bracket bending method. The force levels in loading plateau (LP) and unloading plateau (UP) were determined. One-way ANOVA and Duncan post-hoc were used for data analysis. Result: In group A, LP and UP showed no statistical significant change. In Group B, steam heat decreased LP and UP but dry heat increased UP significantly. In Group C, steam and dry heat decreased UP and LP significantly. Conclusion: It seems that heat sterilization could alter the L/D properties of some H-A wires depending on the type of wires and sterilization method.